Ôn tập toán 8

Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
Đặng Khánh Ngọc

1;  Chứng minh:

a) (x-1)(x^2+x+1)=x^3-1

b)(x^3+x^2y+xy+y^3)(x-y)=x^4-y^4

Trần Việt Linh
31 tháng 8 2016 lúc 21:20

a) Biến đổi vế trái ta có:

\(\left(x-1\right)\left(x^2+x+1\right)=x^3+x^2+x-x^2-x-1=x^3-1=VP\)

=>đpcm

b)Sai đề phải là \(\left(x^3+x^2y+xy^2+y^3\right)\left(x-y\right)=x^4-y^4\)

Biến đổi vế trái ta có:

\(\left(x^3+x^2y+xy^2+y^3\right)\left(x-y\right)=x^4-x^3y+x^3y-x^2y^2+x^2y^2-xy^3+xy^3-y^4\\ =x^4-y^4=VP\)

=>đpcm


Các câu hỏi tương tự
Võ Thị Mai Thơm
Xem chi tiết
Võ Đông Anh Tuấn
Xem chi tiết
Nguyễn Thùy Linh
Xem chi tiết
Nguyễn Thị Mỹ Lệ
Xem chi tiết
Duong Thi Nhuong
Xem chi tiết
Võ Thị Mai Thơm
Xem chi tiết
Dương Thị Thu Trà
Xem chi tiết
Nguyễn Thùy Linh
Xem chi tiết
Duong Thi Nhuong
Xem chi tiết